Influence Of Maternal Anthropometric Characteristics on Birth Weight of Newborn - Khushboo Juneja; Najam Khalique; M Athar Ansari; Anees Ahmad; Mohd Haroon Khan; Shahin Rehman (Medsci Publications, 2016)
Background: Birth weight is an indicator of health and nutritional status of mothers as well as predictor of infant health and devel- opment. Objective: To find out influence of maternal anthropometric char- acteristics on Birth weight. Methods: The present Community based prospective study was conducted in the field practice areas of Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh, Uttar Pradesh. Registered pregnant women who were in their first trimester and whose Expected Date of De- livery lie within our study period of one year were considered for study.Data was analyzed using SPSS version 20. Percentages, and Chi Square Test used. Results: Prevalence of LBW was found to be 40%. The mean birth weight of all the 160 newborns was 2.58 kg (with SD ±0.55 kg). Sta- tistically significant association was found between height, weight gain and birth weight of newborn. Conclusion: Nutritional status of mother has to be improved not only during pregnancy, but also in her early childhood by under- taking food supplementation programs implemented through Na- tional Health Programs that improve the weight gain during de- livery and result in improved fetal outcome.